Some features of source rock oil production - D. A. Ivanov (Наука. Инновации. Технологии, 2025)
The paper describes the current state of source rock oil production in the world and the current state of research. Production from source-rocks is generally characterized by two consecutive pseudosteady state flows from the fractured and the matrix media. The dynamic material balance method is used to analyze production data for wells that produce in a pseudo-steady-state from one sourcerock field in Western Siberia. The analysis allowed us to determine the volume of drained reserves separately from the fractured medium (including secondary fractures from hydraulic fracturing) and the matrix medium. Based on the results of the analysis, a third pseudosteady-state regime with an increased volume of drained reserves was determined for individual wells at a later stage of production. The third mode is characterized by an increase in the density of the produced oil products and has not been previously described in the literature. The most likely source of an additional denser fluid is the bituminous organic matter, which in its primary state is in a solid adsorbed form. These phenomena can occur only in source-rock, where there is an abundance of bituminous organic matter in a solid adsorbed and liquid dissolved state. It is not possible to describe the entire nature of what is happening at the current stage, but full description will include a combination of effects including the expansion of fluids, the interaction of hydraulic fracturing fluid with rock and rock cracking due to depression with a change in the geometry of the pore space during development. These phenomena are typical only for individual horizontal wells with multistage hydraulic fractioning and are not present, for example, when producing from vertical wells without hydraulic fracturing.